Perancangan Media Pembelajaran Fisika - Pemuaian - Melissa Angga Ng; Mei Shen (Jurnal Informatika dan Sistem Informasi, 2015)
Physics theory such as the theory of thermal expansion and contraction found difficult and less motivating for some students. Multimedia technology seen as an opportunity to resolve those kind of problem in physics education. Multimedia technology has the capability to show subjects in different lights such as show process which is unseen, provide simulation to explain subject more clearly and divide complex explanation into chunks. Phases of interview, analyzing and design had been conduct in order to build a digital media to assist student to learn independently.